A model of an accessibility curriculum in higher education - Weeden, Elissa (Frontiers in Computer Science, 2023)
Individuals may face daily unnecessary challenges and barriers in digital and physical spaces and in the use of products, which can result in exclusion. As a society, we need to do better regarding accessibility. One step toward removing challenges and barriers to a more accessible and inclusive society is to increase awareness and knowledge around accessibility. Toward that end, a four-year private technical university in the northeast United States has offered a four-course curriculum dedicated to accessibility. This curriculum, instruction, and pedagogy paper will describe the design and delivery of the four-course accessibility curriculum consisting of Design for Accessibility, Access and Assistive Technology, Accessibility Through the Lifespan, and Research in Accessibility. This model curriculum aims to educate students to mindfully consider, advocate, and increase accessibility as they prepare to enter the workforce to create digital and physical spaces and products.